Grid-Connected PV System with Quasi-Z-Source Inverter And ANFIS MPPT - J. Raji; S. Lakshmi; S. Prakash (International Journal of Sustainable Engineering Innovations, 2025)
Background of Study: The integration of photovoltaic (PV) systems into the power grid is a key step in the transition toward renewable energy. However, challenges such as inconsistent power output, inefficient energy harvesting, and synchronization with the grid limit their effectiveness. Addressing these issues is crucial for reliable and sustainable solar energy utilization. Aims and Scope of Paper: This study introduces an ANFIS-based MPPT strategy to boost PV efficiency and grid stability, focusing on intelligent control and advanced inverter systems for seamless AC integration. Methods: The system uses an ANFIS-based MPPT to dynamically adjust the DC-DC converter’s duty cycle, integrates a Switched Quasi-Z-Source Inverter (SQZSI) for voltage boosting and reliability, employs a single-phase VSI with LC filters to produce smooth AC output, and applies a PI controller for grid voltage and frequency synchronization. Result: The system demonstrated improved energy harvesting efficiency and grid stability. The ANFIS algorithm enabled accurate and rapid tracking of the maximum power point, while the inverter architecture ensured consistent and high-quality power delivery compatible with grid standards. Coclusion: The combination of ANFIS-based MPPT, SQZSI, and synchronized control provides a reliable and efficient solution for integrating solar energy into the modern power grid. This intelligent, robust system enhances both performance and sustainability in renewable power generation.